2013
DOI: 10.1002/oby.20284
|View full text |Cite
|
Sign up to set email alerts
|

Associations of body fat percent and body mass index with childhood asthma by age and gender

Abstract: Objective: High body mass index (BMI) has been shown to be associated with asthma, but the pattern of this association is still unclear and may differ by gender or stage of puberty. BMI is only a proxy of adiposity, whereas estimation of body fat percent (BF%) by the bioimpedance technique is considered an accurate measure of adiposity. We investigated whether BMI and BF% behave differently in their association with asthma between genders, before and during adolescence. Design and Methods: In this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Hacihamdioglu et al add that a neck circumference over the ninetieth percentile is associated with severe asthma in children -severe asthma was defined as children who needed Step three, Step four, or Step five treatment options according to the Global Initiative for Asthma guidelines [15]. Body fat percentage, one more index for obesity, displays a U-shaped association with asthma instead of the linear association between asthma and Body Mass Index therefore implying a greater risk of asthma for both lower and higher body fat percentages [16].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 99%
“…Hacihamdioglu et al add that a neck circumference over the ninetieth percentile is associated with severe asthma in children -severe asthma was defined as children who needed Step three, Step four, or Step five treatment options according to the Global Initiative for Asthma guidelines [15]. Body fat percentage, one more index for obesity, displays a U-shaped association with asthma instead of the linear association between asthma and Body Mass Index therefore implying a greater risk of asthma for both lower and higher body fat percentages [16].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 99%
“…A total of seven studies presented data on the number of cases and non-cases in underweight and normal BMI groups comprising a total of 772,040 children (7,(41)(42)(43)(44)(45)(46). The summary risk estimate of the studies showed that there was a significant decrease odds of wheezing disorders (OR = 0.85, 95% CI: 0.75 to 0.97; p = 0.02) for the underweight children ( Fig.…”
Section: Underweight and Childhood Wheezing Disordersmentioning
confidence: 99%
“…A total of 29 studies presented data on the number of cases and non-cases in the overweight and normal BMI groups that included a total of 1,075,042 children (7,8,(41)(42)(43)(44)(45)(46)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). The summary of the ORs showed that there was a significant increased risk of wheezing disorders (OR: 1.23, 95% CI: 1.17-1.29; p < 0.001) ( Fig.…”
Section: Overweight and Childhood Wheezing Disordersmentioning
confidence: 99%
“…It was concluded that the body fat percentage was significantly higher in the children with BA in the age of 7-8 years and 16-17 years, but not in the age groups in between [56].…”
Section: Resultsmentioning
confidence: 91%